Exporting Black Gold Means Importing Power Outages: The Juridical Failure of Indonesia's Coal Distribution Governance - Irsan Rahman (Sangia Nibandera Law Research, 2026)
Indonesia, as the world’s largest exporter of thermal coal, experienced rolling blackouts across Java in June 2026, affecting power generation capacity by up to 2 GW a paradox that illustrates the legal failure of the Domestic Market Obligation (DMO) policy. This study aims to analyse the structural, governance and policy failures within the DMO framework in ensuring national energy security. The study employs a normative legal method (doctrinal legal research), utilising legal, conceptual and case-based approaches, whilst analysing primary legal sources. The findings reveal three interrelated levels of failure. Firstly, structural and legal failures: the fixed price cap of US$70 per tonne, which has remained unchanged since 2018, creates an “Export Premium Paradox” whereby the law mandates compliance, whilst the market actually incentivises non compliance through a price differential of US$54 78 per tonne between domestic and global prices, thereby undermining the normative effectiveness of the legislation. Secondly, governance failures: production restrictions (the 400 million tonne cap set by the RUEN versus actual production of 817 million tonnes), bureaucratic obstacles within the RKAB, weak law enforcement lacking credible deterrents, and systemic corruption (exposed through the KPK’s investigation into mining permits) exacerbate the DMO’s legal shortcomings. Thirdly, policy failure: reactive crisis management such as export bans, production cuts and blending regulations merely addresses temporary symptoms, whilst the underlying price-setting mechanism remains unreformed. This theoretical contribution demonstrates that a static regulatory framework collapses under dynamic market conditions, thereby challenging the command-and-control approach. This study recommends six reforms: dynamic price setting linked to the HBA benchmark; quality specifications; production coordination aligned with the RUEN; enhanced law enforcement with proportionate sanctions; anti-corruption measures; and a constitutional review based on Article 33(3). This case offers broader lessons for resource-rich developing countries: legal certainty and proportionality.